Effects of Aroclor 1254 and vitamin E on arginase activity in adult, pregnant rats and their offsprings - Dogan, Ayse; Erisir, Mine (Ankara Univ Press, 2017)
This study examined the effect of Aroclor 1254 on arginase activity and protective role of vitamin E among adult rats, pregnant rats and their offsprings. Totally 90 Sprague-Dawley rats were divided into three main groups as 30 pregnant, 30 adult and 30 offsprings (pups of the pregnant rats) based on the treatments administered during the pregnancy period (20 days) with subcutaneous daily injections of Aroclor 1254 (2 mg/kg/day) alone or associated with vitamin E (50 mg/kg/day) or normal saline in controls. Female rats and their offsprings (10 offsprings per groups) were analyzed in terms of the arginase activity in liver. A statistically significant increase was determined in liver arginase activity of adult rats exposed to Aroclor 1254 (p<0.05). Vitamin E administered simultaneously with Aroclor enabled liver arginase activity of adult rats to approach statistically normal values. A statistically insignificant increase was found in the arginase activity among pregnant rats and offsprings. While vitamin E administered simultaneously with Aroclor was ineffective in pregnant rats, it caused a statistically significant increase in offsprings (p<0.05). We recommend that addition of vitamin E can prevent the increase in the liver arginase activity caused by Aroclor 1254.
Aroclor 1254 ve vitamin E’nin yetişkin, gebe rat ve yavrularında arginaz aktivitesi üzerine etkileri
Keywords: Arginase; Aroclor 1254; offspring; pregnant; vitamin E